Ag–CuO–ZnO metal–semiconductor multiconcentric nanotubes for achieving superior and perdurable photodegradation. Issue 32 (3rd August 2017) - Xu, Kaichen; Wu, Jiagen; Tan, Chuan Fu; Ho, Ghim Wei; Wei, Ang; Hong, Minghui
Abstract : A ternary hetero-nanostructured Ag–CuO–ZnO nanotube composite exhibits a great enhancement of photocatalytic activity and ultra-high photostability in pollutant degradation. Abstract : Solar energy represents a robust and natural form of resource for environment remediation via photocatalytic pollutant degradation with minimum associated costs. However, due to the complexity of the photodegradation process, it has been a long-standing challenge to develop reliable photocatalytic systems with low recombination rates, excellent recyclability, and high utilization rates of solar energy, especially in the visible light range. In this work, a ternary hetero-nanostructured Ag–CuO–ZnO nanotube (NT) composite is fabricated via facile and low-temperature chemical and photochemical deposition methods. Under visible light irradiation, the as-synthesized ZnO NT based ternary composite exhibits a greater enhancement (∼300%) of photocatalytic activity than its counterpart, Ag–CuO–ZnO nanorods (NRs), in pollutant degradation. The enhanced photocatalytic capability is primarily attributed to the intensified visible light harvesting, efficient charge carrier separation and much larger surface area. Furthermore, our as-synthesised hybrid ternary Ag–CuO–ZnO NT composite demonstrates much higher photostability and retains ∼98% of degradation efficiency even after 20 usage cycles, which can be mainly ascribed to the more stable polar planes of ZnO NTs than those of ZnO NRs. These results afford a new route to construct ternary heterostructured composites with perdurable performance in sewage treatment and photocorrosion suppression.